Methanogens in the Antarctic Dry Valley permafrost. Issue 8 (5th June 2018) - Vishnivetskaya, Tatiana A; Buongiorno, Joy; Bird, Jordan; Krivushin, Kirill; Spirina, Elena V; Oshurkova, Victoria; Shcherbakova, Victoria A; Wilson, Gary; Lloyd, Karen G; Rivkina, Elizaveta M
ABSTRACT: Polar permafrost is at the forefront of climate change, yet only a few studies have enriched the native methane-producing microbes that might provide positive feedbacks to climate change. Samples Ant1 and Ant2, collected in Antarctic Miers Valley from permafrost sediments, with and without biogenic methane, respectively, were evaluated for methanogenic activity and presence of methanogens. After a one-year incubation of both samples under anaerobic conditions, methane production was observed only at room temperature in microcosm Ant1 with CO2 /H2 (20/80) as carbon and energy sources and was monitored during the subsequent 10 years. The concentration of methane in the headspace of microcosm Ant1 changed from 0.8% to a maximum of 45%. Archaeal 16S rRNA genes from microcosm Ant1 were related to psychrotolerant Methanosarcina lacustris . Repeated efforts at achieving a pure culture of this organism were unsuccessful. Metagenomic reads obtained for the methane-producing microcosm Ant1 were assembled and resulted in a 99.84% complete genome affiliated with the genus Methanosarcina . The metagenome assembled genome contained cold-adapted enzymes and pathways suggesting that the novel uncultured Methanosarcina sp. Ant1 is adapted to sub-freezing conditions in permafrost. This is the first methanogen genome reported from the 15 000 years old permafrost of the Antarctic Dry Valleys. Abstract : The genome of methanogen Ant1 of the genus Methanosarcina reported for the first time from the 15 000 years old permafrost of the Antarctic Dry Valleys contains proofs of cold-adapted enzymes and pathways.